Transfer in the acquisition of idiomatic expressions in French as a Foreign Language - Cáceres Guerrero, Luz Dary (Rastros Rostros, 2017)
Introduction: this investigation examines to what extent non-native students use the knowledge of their first language (L1) to understand and produce idiomatic expressions in the second language (L2).Methodology: twenty six Colombian students of French (Level B2) and twenty six Hispanic students living in Toulouse (level C1) took part in this study. Thirty idiomatic expressions classified in three categories were evaluated: a) similar in form and meaning to an equivalent ex-pression in Spanish, b) similar to an equivalent expression in Spanish, c) different from an equivalent expression in Spanish. Four tests were made: two production tests, a reception test and a comprehension test.Results: to test the linguistic transfer hypothesis that identical expressions are easy to understand and pro-duce, while the different expressions present more difficulties in both skills (com-prehension and production), the category of similar expressions would thus nuance the transfer hypothesis, and that, particularly in terms of semantic opacity, frequency, structure and lexicon.Conclusion: the didactic approach in French as Foreign Language (FFL) must start from what the students know so that as part of their process of L2 acquisition, they address the particularities and differencesbetween L1 and L2.
Keywords: adquisición; expresiones idiomáticas; francés como lengua extranjera; transferencia lingüística